Pelaksanaan Registrasi Kematian dan Penyebab Kematian di Kota Ambon Tahun 2014 - Eva Sulistiowati; Kartika Handayani (Media Penelitian dan Pengembangan Kesehatan, 2019)
Abstract The registration system of death and cause of death as part of a good Civil Registration and Vital Statistics System (CRVS) form the basis for planning, monitoring and evaluating development programs. Ambon City as one of the development areas for recording death and causes of death since 2010 shows results that are still under-estimated (below 7 permill). Evaluation of the implementation process is needed to find out the obstacles. The qualitative methods include in-depth interviews, Focus Group Discussion (FGD) and collecting secondary data as supporting data. The analysis is part of the Comprehensive Evaluation Study on the Development of the Death Registration System and the Causes of Death in 14 districts/cities in Indonesia in 2014, carried out by triangulation and thematically compiled. The results obtained that the system of birth and death registration in the city of Ambon is already well-organized: there are regional regulations regarding the administration of population administration even though they have not included information on causes of death; the difference in vital registration data from various agencies; limited human resources, funds, facilities and infrastructure; and public awareness to report births/deaths still low. To increase the coverage of death registration and causes of death, it is necessary: local government regulations that include the cause of death; formation of joint committees and “one data” vital statistics; Autopsy Verbal (AV) workshop/training; utilization of funds from the Regional Revenue and Expenditure Budget and Health Operational Costs optimally; cooperation with community leaders (Muhabet) and socialization to the community. Abstrak Sistem registrasi kematian dan penyebab kematian sebagai bagian dari Sistem Registrasi Sipil dan Statistik Vital (Civil Registrations and Vital Statistics/CRVS) yang baik menjadi dasar untuk perencanaan, monitoring, dan evaluasi program pembangunan. Kota Ambon sebagai salah satu daerah pengembangan kegiatan pencatatan kematian dan penyebab kematian sejak tahun 2010, menunjukkan hasil yang masih under estimate (dibawah 7 permil). Evaluasi proses pelaksanaan diperlukan untuk mengetahui kendala yang dihadapi. Metode yang digunakan kualitatif meliputi wawancara mendalam, Focus Group Discussion (FGD) dan mengumpulkan data sekunder sebagai data pendukung. Analisis merupakan bagian dari Studi Evaluasi Menyeluruh Pengembangan Sistem Registrasi Kematian dan Penyebab Kematian di 14 kabupaten/kota di Indonesia Tahun 2014, dilakukan dengan triangulasi dan disusun secara tematik. Hasil yang diperoleh bahwa sistem pencatatan kelahiran dan kematian di Kota Ambon sudah tersistem dan tertata cukup baik, ada peraturan daerah tentang penyelenggaraan administrasi kependudukan walaupun belum mencakup keterangan penyebab kematian; adanya perbedaan data registrasi vital dari berbagai instansi; keterbatasan sumber daya manusia, dana, sarana prasarana; serta kesadaran masyarakat untuk melaporkan kejadian kelahiran/kematian yang masih rendah. Untuk meningkatkan cakupan registrasi kematian dan penyebab kematian, diperlukan: regulasi pemerintah daerah yang menyertakan penyebab kematian; pembentukan komite bersama dan “one data” statistik vital; workshop/pelatihan Autopsy Verbal (AV); pemanfaatan dana Anggaran Pendapatan dan Belanja Daerah (APBD) dan Biaya Operasional Kesehatan (BOK) secara optimal; kerjasama dengan tokoh masyarakat (Muhabet), dan sosialisasi kepada masyarakat.